Vitamin D Mitigates Inflammation and Downregulates Importin α3 in Non-Alcoholic Fatty Liver Disease (NAFLD) - Ashok Kujur; S. John Mary*; Delinta D; Ajila A; Jesuraj P; Christina C; Gunasekar C.J (International Journal of Cheminformatics, 2026)
Background: Pro-inflammatory cytokines, such as TNF-α, IL-1β, IL-6, and IL-8, seem to play a crucial role in the progression of NAFLD as they activate the transcription factor NF-кB. The activated NF-кBp50/RelA subunits are translocated to the nucleus by Importin α3 and Importin α4. Numerous studies have indicated a negative association between NAFLD and vitamin D levels. Low vitamin D levels have been correlated with histological severity, necro-inflammation, and fibrosis in NAFLD. Non-alcoholic fatty liver disease (NAFLD) affects about one-third of the population in the United States and Western countries, reaching up to 90% among obese individuals and those undergoing bariatric surgery. Characterized by hepatic fat accumulation, NAFLD progresses from simple steatosis to non-alcoholic steatohepatitis (NASH), fibrosis, and, in rare cases, hepatocellular carcinoma. Linked intricately with metabolic syndrome, including diabetes and obesity, NAFLD development involves insulin resistance and hyperinsulinemia. Experimental evidence consistently associates low vitamin D levels with NAFLD severity, independent of age, gender, and BMI. Pro-inflammatory cytokines, such as TNF-α and IL-6, play critical roles in NAFLD, with positive correlations between liver fibrosis and TNF-α levels in NASH patients. The inflammatory cascade involves NF-κB activation, Importin α3, and Importin α4. Vitamin D emerges as a key player, up-regulating the NF-κB inhibitor IкBα and reducing pro-inflammatory activity. Studies in NASH models highlight vitamin D's positive impact on inflammation, fibrosis, and insulin resistance. Recent research underscores calcitriol's role in decreasing Importin α3 expression, influencing NF-κB translocation. This study provides novel insights into calcitriol's effects on Importin α3 and IκBα in HepG-2 cells, unraveling cellular and molecular mechanisms in the intricate interplay between vitamin D and NAFLD pathology. Objective: Vitamin D may resolve the ongoing inflammation observed in NAFLD by reducing the effects of pro-inflammatory cytokines that are extensively produced in NAFLD. Methods: “HepG-2 cell cultures were subjected to calcitriol stimulation, both in the presence and absence of pro-inflammatory cytokines alongside the anti-inflammatory cytokine IL-10. Quantitative polymerase chain reaction (qPCR) was employed to assess mRNA expression levels of Importin α3 and Importin α3. Additionally, immunofluorescence was utilized for antibody detection.” Results: Pro-inflammatory cytokines significantly increase the mRNA and protein expression of Importin-α3 in HepG2 cells. Treatment of HepG-2s with calcitriol significantly decreases the mRNA and protein expression of Importin-α3 and attenuates the effects of pro-inflammatory cytokines. Conclusion: Our data suggest that, under inflammatory conditions, calcitriol plays an inhibitory role in the regulation of NF-кB by decreasing the expression of Importin α3. Thus, calcitriol reduces the translocation of NF-кB and thereby lowers its transcriptional activities.
Keywords: Importin α3; NAFLD; Vitamin D; calcitriol; inflammation; pro-inflammatory cytokines